PENGARUH PERMAINAN DAKON TERHADAP PERKEMBANGAN KOGNITIF MATEMATIK PADA ANAK USIA DINI DI RA AL-IKHWAN KOTA TASIKMALAYA - Rosmiati Rosmiati; Asep Mumung; Rostika Srihilmawati (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2020)
The education of early childhood has a development and growth which must be enhanced. One of the duty growth is cognitive growth. Cognitive growth has eight intelligence aspects one of the intelligence is logical mathematics intelligence. One of the learning concept in early childhood is learning while playing. So that, learning with Dakon Geometry Game could help the child to think logical mathematics. the purpose of this to improve the cognitive development of childrens mathematics intelligence in B group of early childhood at B RA Al-Ikhwan Tasikmalaya. The results of this study found that 7 people began to develop as much as 70% and 3 people developed as much as 30%. So, it can be concluded that there is difference influence which is significance between Dakon Geometry Game towards of logical mathematics intelligence in B group of early childhood at B RA Al-Ikhwan Tasikmalaya.